(untitled) (REMUNOM, 2023)
The text discurse the inclusion of people with disabilities in the job market, a right guaranteed by specific legislation, such as the Brazilian Law on Inclusion in Companies (Law nº 8,213/1991). The law establishes that companies with more than 100 employees must fill a portion of their positions with people with disabilities. A descriptive study carried out in the municipality of Linhares, in Espírito Santo, investigated the perception of Human Resources professionals from an industrial company in the furniture industry regarding the hiring of people with disabilities. The qualitative study revealed that the company has not adapted its criteria for the professional advancement of people with disabilities. The research highlights that inclusion in the job market goes beyond simple hiring and involves overcoming physical, attitudinal, economic and cultural obstacles that perpetuate the disadvantage faced by People with Disabilities (PWD). It is concluded that it is crucial to create more inclusive environments, not only to comply with legislation, but also to provide equal opportunities to professionals with disabilities.